BLOOD GAS AND TOXICOLOGICAL ANALYSIS IN ASPHYXIAL DEATHS: A CROSS-SECTIONAL STUDY - Dr Muhammad Shafay; Dr Roman Ashraf; Dr Rabail Altaf; Dr Ishrat Bibi; Dr Farooq Ahmed Abro; Dr Nazia Yasmin (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Asphyxial deaths remain a significant concern in forensic medicine due to their sudden, often preventable nature and complex medico-legal implications. Understanding the demographic profile, causes, and toxicological aspects of such deaths is crucial for effective prevention, investigation, and policy-making. Objective: To determine the frequency and types of poisons contributing to asphyxial deaths and analyze their demographic, clinical, and postmortem patterns in medico-legal autopsies conducted in the Rawalpindi and Islamabad region. Methodology: This descriptive cross-sectional study was conducted at the Department of Forensic Medicine and Toxicology, HBS Medical & Dental College, Islamabad, over a period of one year. A total of 52 cases of asphyxial deaths confirmed via autopsy and toxicological analysis were included using non-probability consecutive sampling. Detailed examination of demographics, manner of death, autopsy findings, and toxicology reports was carried out. Data were analyzed using SPSS version 25. Results: Males constituted 73.1% of cases, with the highest frequency in the 31–45-years age group (36.5%). Urban residents accounted for 59.6% of deaths. The majority (48.1%) were accidental, followed by suicidal (32.7%) and homicidal (19.2%) deaths. External findings included cyanosis (80.8%) and petechial hemorrhages (75%). Toxicological analysis revealed carbon monoxide (32.7%) as the most common toxin, followed by organophosphates (15.4%), methanol (11.5%), and cyanide (9.6%). Conclusion: Carbon monoxide, organophosphates, and methanol are major toxic agents in asphyxial deaths, particularly among adult urban males. Strengthening occupational safety regulations and public awareness can significantly reduce such preventable fatalities.